CEO’s gender, power, ownership: roles on audit report lag / Sarini Azizan - Azizan, Sarini (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This study examines the role of CEO’s gender, power and ownership on audit report lag. The rapid changes of market regulations and societal norms make CEO’s characteristics emerge as evolving risk factors for corporate governance and audit research. This raises the importance for research to understand their dynamic influences on corporate financial disclosure quality specifically, timeliness. This study hypothesises that different CEO’s characteristics set different tones to the audit discussion in the boardroom. To test the hypothesis, this study uses multiple secondary data from Compustat, Audit Analytics Execucomp and BoardEX and STATA analytical solution. The CEO’s characteristics are divided into three dimensions that measure gender diversity, power and ownership concentration. This study provides evidence that both CEO’s ownership and power, which proxied by (1) industrial experience and (2) social network size are significantly associated with audit report lag. However, only the association with the CEO’s power reduces audit report lag whereas CEO’s ownership increases it. With regards to the gender diversity, it is only effective in reducing audit report lag if other CEO’s characteristics are also presence. Overall, the results provide support to the study proposition in respect of the role of CEO’s characteristics in accelerating financial reporting timeliness.